Digital Tools and the History of Political Thought: The Case of Jean Bodin. (1st November 2015) - Evrigenis, Ioannis D.
Abstract : As scholars debate the virtues, drawbacks, and even the existence of the digital humanities, it is worth thinking more narrowly about how certain digital tools might be put to use in the study of the history of political thought. In what follows, I examine the case of Jean Bodin's Les six livres de la république, a work as challenging as it is important. By means of examples of the development of that work and of certain relatively new techniques, I consider the opportunities that these tools afford us for the composition of digital variorum editions that are broadly collaborative, fully accessible, up-to-date, and featuring a heretofore impossible degree of editorial accountability.